Assessment of photocatalytic, superhydrophobic and self-cleaning properties on hot mix asphalts coated with TiO2 and/or ZnO aqueous solutions. (30th March 2018) - Rocha Segundo, I.; Ferreira, C.; Freitas, E.F.; Carneiro, J.O.; Fernandes, F.; Júnior, S. Landi; Costa, M.F.
Highlights: Photocatalytic, superhydrophobic and self-cleaning capabilities were promoted on asphalt mixtures. AC 6 and AC 14 mixtures were coated with TiO2 and/or ZnO aqueous solutions by spraying. Physicochemical and morphological properties of bitumen samples were evaluated by FTIR and AFM. New pavement surface capabilities assessed with Water Angle Contact and Photocatalytic Efficiency tests. No deterioration was guaranteed for AC 14 TiO2, AC 14 TiO2 ZnO, AC 6 TiO2 and AC 6 TiO2 ZnO solutions. Abstract: Photocatalytic, superhydrophobic and self-cleaning capabilities were promoted on AC 6 and AC 14 asphalt mixtures by spraying of TiO2 and/or ZnO. Initially, physicochemical and morphological properties of bitumen samples were evaluated by Fourier Transform Infrared Spectroscopy and Atomic Force Microscopy after the solution spraying of TiO2, ZnO and TiO2 ZnO. Then, to assure those capacities, Water Angle Contact and Photocatalytic Efficiency tests were carried out on both mixtures. Finally, mixtures were assessed mechanically through Indirect Tensile Strength. Photocatalytic, superhydrophobic and self-cleaning properties were guaranteed for AC 14 with TiO2 and TiO2 ZnO and AC 6 with TiO2 ZnO without deteriorations.